Delighting the Customer: Creativity-Oriented High-Performance Work Systems, Frontline Employee Creative Performance, and Customer Satisfaction. (February 2019) - Martinaityte, Ieva; Sacramento, Claudia; Aryee, Samuel
Drawing on self-determination theory, we proposed and tested a cross-level model of how perceived creativity-oriented high-performance work systems (HPWS) influence customer satisfaction. Data were obtained from frontline employees (FLEs), their managers, and branch records of two organizations (retail bank and cosmetics) in Lithuania. Results of multilevel structural equation modeling analyses revealed partial support for our model. Although perceived creativity-oriented HPWS related to creative performance at the individual level, this effect was mediated solely by need satisfaction and not by creative process engagement nor by a serial mediation of both variables as we hypothesized. However, as we did hypothesize, average branch creative performance related to branch customer satisfaction. We interpret our findings as underscoring the utility of perceived creativity-oriented HPWS in fostering FLEs' creative performance and ultimately, customer satisfaction.